The Effect of Inflation, Exchange, SBI Interest Rate and Dow Jones Index on JCI on IDX 2013 – 2018 - Hasanudin Hasanudin (Budapest International Research and Critics University, 2021)
This analysis aims to display inflation, exchange rates of currencies, SBI, and the Dow Jones Index on IHSG and IDX from 2013 to 2018. Quantitative testing approaches using the SmartPLS 3 technology and Structural Equation Modeling (SEM) analysis techniques. Inflation has a large positive effect on the JCI. Which indicates that as inflation rises, the JCI value falls. Exchange rates significantly impact the JCI. Therefore, the exchange rate indicator directly affects the path of the high exchange rate, which reduces the JCI figure. The SBI rate has no Impact and negative on JCI. This means JCI would not be affected by the increased number of SBI interest rates. For the Dow Jones Index, the JCI is significantly positive. Which suggests that the Dow Jones index's rise has an effect on the JCI. The Dow Jones Index has the most impact on work motivation, at 0.982, in contrast to the inflation, exchange rate, and SBI interest rate variables against the IHSG of IDX from 2013 to 2018.